Doctor talk at consultancy in English and Vietnamese: An interpersonal comparison = Giao tiếp của bác sĩ trong tư vấn khám bệnh trong tiếng Anh và tiếng Việt: So sánh từ bình diện liên nhân. Degree of doctor of Linguistics: 92202 - Nguyễn, Thanh Nga (2019)
The language that doctors use during their consultations with patients has been the focus of increasing interest for many years. A large number of contributors to this field of medicine, which include linguistic researchers, have explored this domain in various perspectives and in different languages. This thesis examined the issue of doctor talk, a subject that has been discussed by a large literature of medical communication. This thesis employed Systemic Functional Linguistics (hereafter SFL) as the theoretical and analytical framework.